Development and validation of a rapid, aldehyde dehydrogenase bright–based cord blood potency assay - Shoulars, Kevin (Blood, 2016)
Banked, unrelated umbilical cord blood provides access to hematopoietic stem cell transplantation for patients lacking matched bone marrow donors, yet 10% to 15% of patients experience graft failure or delayed engraftment. This may be due, at least in part, to inadequate potency of the selected cord blood unit (CBU). CBU potency is typically assessed before cryopreservation, neglecting changes in potency occurring during freezing and thawing. Colony-forming units (CFUs) have been previously shown to predict CBU potency, defined as the ability to engraft in patients by day 42 posttransplant. However, the CFU assay is difficult to standardize and requires 2 weeks to perform. Consequently, we developed a rapid multiparameter flow cytometric CBU potency assay that enumerates cells expressing high levels of the enzyme aldehyde dehydrogenase (ALDH bright [ALDH(br)]), along with viable CD45(+) or CD34(+) cell content. These measurements are made on a segment that was attached to a cryopreserved CBU. We validated the assay with prespecified criteria testing accuracy, specificity, repeatability, intermediate precision, and linearity. We then prospectively examined the correlations among ALDH(br), CD34(+), and CFU content of 3908 segments over a 5-year period. ALDH(br) (r = 0.78; 95% confidence interval [CI], 0.76-0.79), but not CD34(+) (r = 0.25; 95% CI, 0.22-0.28), was strongly correlated with CFU content as well as ALDH(br) content of the CBU. These results suggest that the ALDH(br) segment assay (based on unit characteristics measured before release) is a reliable assessment of potency that allows rapid selection and release of CBUs from the cord blood bank to the transplant center for transplantation.